Development of nutritionally enhanced fish burgers: Integrating Atlantic bonito (Sarda sarda) with seaweed and hydrocolloids for sustainable food innovation - Solinho, Joana (2024)
This study developed an innovative fish burger using Atlantic bonito, an abundant but undervalued species rich in lipids and protein. The burger was enriched with chickpea, seaweed (Spirulina and Fucus vesiculosus), and hydrocolloids (xanthan and carrageenan). Using a Taguchi design, the effects of varying concentrations of these ingredients on the physicochemical properties, texture, phenolic content, and antioxidant activity (DPPH, ABTS) were evaluated. The optimal formulation (2 g/100 g Spirulina, 3 g/100 g Fucus vesiculosus, 0 g/100 g xanthan, 4 g/100 g carrageenan) increased fiber by 1.5 times, protein by 2.8 times, antioxidant activity (ABTS) by 1.2 times, and phenolic content by 3.4 times compared to the control. Seaweed concentration was linked to increased burger hardness, while cohesiveness, adhesiveness, and gumminess were unaffected by hydrocolloid concentration. No significant changes were observed in moisture content or DPPH antioxidant activity. The study demonstrates the potential of using undervalued fish species like Atlantic bonito to create nutritionally enhanced, sustainable food products.